Suppression of endometriosis by miRNA-34a via inhibition of matrix metalloproteinase-2: An alternative pathway to impede invasion - Yasmin Begum; Anuradha Pandit; Devendra Shukla; Rahul Gupta; Pramathes DasMahapatra; Amit Kumar Srivastava; Snehasikta Swarnakar (Non-coding RNA Research)
Matrix metalloproteinases (MMPs) cleave proteins of extracellular matrix thus facilitating cellular invasion and cancer progression. High MMP-2 activity is frequently reported in several diseases including endometriosis and cancer. Endometriosis, though benign causing pain and infertility, rarely culminate into ovarian cancer. New diagnostic markers are needed for early diagnosis and proper therapeutic avenues since the only diagnostic method is laparoscopy to date. Emerging evidence shows the importance of MMP activity and involvement of noncoding RNA, e.g. miRNA thereon. We investigated the role of miRNA-34a in MMP-2-mediated regulation of invasion and tumorigenesis in endometriosis. Database analysis showed a decreased miRNA-34a in different gynecological malignancies. qRT-PCR with human endometriotic and control tissues revealed a significant elevation in MMP-2 activity with downregulated miR-34a in diseased individuals proving an inverse correlation between miRNA-34a and MMP-2. Luciferase assay in SK-OV-3 cells demonstrated that miRNA-34a-5p directly binds the 3′UTR of the MMP-2 promoter to reduce its transcription followed by suppression of invasion. The zymographic assay also showed a reduced MMP-2 activity upon miR-34a treatment in End1/E6E7 and SK-OV-3 cells. We also found that miRNA-34a-5p inhibits invasion, migration, colony/spheroid formation, and stemness of the cells thereby reducing in vitro tumorigenesis. Subsequently, the immunoblotting results confirmed that MMP-2, and mesenchymal markers like n-cadherin, vimentin, and slug expression were downregulated, whereas the e-cadherin was upregulated in the cells treated with miRNA-34a mimic. Our study demonstrates the direct binding of miR-34a-5p with the MMP-2 gene's 3′UTR and thus repressed its transcription as well as suppressing endometriosis progression.